Employing Different Writing Tasks to Support Genre Awareness in a Nursing Writing Emphasis Course - Lateefah A. Collingwood; Aimee C. Mapes (Prompt: A Journal of Academic Writing Assignments, 2026)
The literature review and appraisal assignment is a core foundational component of the writing emphasis course for undergraduate nursing students. The assignment traditionally focuses on navigating databases to locate scholarly research, synthesizing research findings across the literature, and learning APA format. Often, however, students conflate effective writing in the discipline as demonstration of correct APA format. This essay describes a pedagogical innovation that integrates reflective writing and a multimodal infographic component. The changes shift the student focus toward communicating evidence-based, person-centered care, which also promotes metacognition and genre awareness as students connect scholarly literature to culturally congruent care in their future clinical practice.